Purification and Properties of Glutamine Synthetase in Leaves and Roots of Pinus banksiana Lamb - Vézina, Louis.-P. (1990)
A method is described for the purification of glutamine synthetase (GS; EC. 6.3.1.2) from the leaves and roots of Pinus banksiana Lamb., a conifer which utilizes ammonium as its primary nitrogen source. The enzyme was purified to apparent homogeneity by a procedure involving salt fractionation as well as ion-exchange, size exclusion, and affinity chromatography. Since the final preparation produced two bands on SDS polyacryamide gels but only one band on a nondenaturating gel, it is concluded that the two subunits (44 and 40 kilodaltons, respectively) are part of a single enzymatic protein which shows GS activity. The pH optimum for leaf GS ranged between 6.2 and 6.5, one pH unit lower than the values reported for higher plants which utilize primarily nitrate nitrogen. Magnesium requirements for GS in P. banksiana were different for leaves and roots, showing V(max)/2 values of 2.5 and 8 millimolar, respectively at 5 millimolar ATP. Furthermore, K(m) values for ammonium were higher for the enzyme in leaves (33.1 micromolar) than in roots (19.2 micromolar). K(m) values for ATP and for glutamate, on the other hand, were similar for the two tissues. A polyclonal antibody was produced against the purified leaf GS. Western blots of leaf homogenates produced two bands, the lighter one being more abundant. The same pattern was found when immunodetection was performed using an anti GS IgG produced against purified GS from Phaseolus nodules thus indicating common antigenic determinants. At least 30% of total GS was recovered in a plastid-fraction of dark-grown calli produced from the basal part of P. banksiana hypocotyls.